Thinking : an interdisciplinary approach to critical and creative thought - Kirby, Gary R.; Goodpaster, Jeffery R. (Upper Saddle River, N.J. : Pearson Prentice Hall, 2007)
Thinking's comprehensive and interdisciplinary approach encourages a more complete and practical treatment for the student of how to think logically, critically, creatively, and persuasively.The authors wrote this book to give teachers and students a friendlier, more comprehensive, more systematic, more interdisciplinary, and thus a more effective text than any on the market.
What Is Thinking? -- Personal Barriers -- Sensing -- Brain and Memory -- Language: Our Thinking Medium -- Feeling -- Creative Thinking -- Organizing -- Logical Thinking -- Scientific Thinking -- Persuasive Thinking -- Problem Solving -- Evaluating -- Decision and Action -- The Challenge to Go on Thinking.
Includes bibliographical references (p. 337-344) and index.
1
Keywords: Thought and thinking